Negative electrode material for lithium-ion secondary battery, method for manufacturing the same, negative electrode for lithium-ion secondary battery, and lithium-ion secondary battery

CN115023828BActive Publication Date: 2026-10-23RESONAC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080095080.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-01-30
Publication Date
2026-10-23
Estimated Expiration
2040-01-30

AI Technical Summary

Benefits of technology

[0036]根据本公开,可提供一种能够制作耐高温性优异、电解液的注液性优异的锂离子二次电池的锂离子二次电池用负极材料及其制造方法、以及使用该负极材料制作的锂离子二次电池用负极和锂离子二次电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115023828B_ABST
    Figure CN115023828B_ABST
Patent Text Reader

Abstract

A negative electrode material for a lithium ion secondary battery includes composite particles having a structure in which a plurality of flat graphite particles are stacked, a particle size distribution D90 / D10 of the composite particles is 2.0 to 5.0, or a particle size distribution D90 / D10 of the plurality of flat graphite particles is 2.0 to 4.4.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to negative electrode materials for lithium-ion secondary batteries and methods for manufacturing the same, negative electrodes for lithium-ion secondary batteries, and lithium-ion secondary batteries. Background Technology

[0002] Lithium-ion rechargeable batteries, leveraging their small size, lightweight design, and high energy density, have long been widely used in electronic devices such as laptops (PCs), mobile phones, smartphones, and tablets. In recent years, against the backdrop of environmental problems such as global warming caused by CO2 emissions, clean electric vehicles (EVs) powered solely by batteries, hybrid electric vehicles (HEVs) combining gasoline engines and batteries, and plug-in hybrid electric vehicles (PHEVs) have become increasingly common. Lithium-ion rechargeable batteries (automotive lithium-ion rechargeable batteries) are used in these EVs, HEVs, and PHEVs. Furthermore, lithium-ion rechargeable batteries have recently been used for energy storage, expanding their applications to multiple fields.

[0003] The performance of the negative electrode material in lithium-ion secondary batteries has a significant impact on the input characteristics of the batteries. Carbon materials are widely used as negative electrode materials for lithium-ion secondary batteries. For example, highly crystallized carbon materials such as artificial graphite and spherical natural graphite (obtained by spheroidizing flake-like natural graphite) have been proposed as materials for obtaining high-density negative electrodes.

[0004] As an example of artificial graphite, International Patent Publication No. 2015 / 147012 discloses a negative electrode material for lithium-ion secondary batteries comprising composite particles, wherein the composite particles contain multiple flat graphite particles and spherical graphite particles aggregated or combined in a manner where the orientation planes are not parallel. Furthermore, Japanese Patent Application Publication No. 2005-302725 discloses a negative electrode active material for lithium secondary batteries, which comprises carbon powder particles having a morphology of plate-like particles stacked along the surface to form a primary stable structure, and having micropores formed on the surface. Summary of the Invention

[0005] The problem that the invention aims to solve

[0006] In lithium-ion secondary batteries, exposure to high temperatures lowers the activation energy for electrolyte decomposition, making it more susceptible to decomposition caused by the negative electrode active material. This decomposition leads to battery capacity reduction due to electrolyte consumption, thus minimizing decomposition is desirable. While conventional carbon materials have achieved improvements in high capacity and cycle performance, there is still room for improvement in suppressing electrolyte decomposition during high-temperature storage.

[0007] Furthermore, commercial vehicles such as buses and delivery vehicles have predictable travel distances, making them relatively easy to electrify. In such commercial vehicles, where operation is primarily during the day, excellent high-temperature resistance is particularly crucial for lithium-ion rechargeable batteries.

[0008] Furthermore, previous technologies have struggled to effectively maintain electrolyte circulation to ensure lithium-ion mobility while suppressing electrolyte decomposition reactions at the interface between the negative electrode material and the electrolyte.

[0009] In view of the above, the present invention aims to provide a negative electrode material for a lithium-ion secondary battery that can produce a lithium-ion secondary battery with excellent high temperature resistance and excellent electrolyte injection properties, as well as a negative electrode for a lithium-ion secondary battery and a lithium-ion secondary battery made using the negative electrode material.

[0010] Methods for solving problems

[0011] The methods used to solve the above problems include the following approaches.

[0012] <1> A negative electrode material for lithium-ion secondary batteries, comprising composite particles having a structure formed by stacking multiple flat graphite particles, wherein the particle size distribution D90 / D10 of the composite particles is 2.0 to 5.0.

[0013] <2> A negative electrode material for lithium-ion secondary batteries, comprising composite particles having a structure formed by stacking multiple flat graphite particles, wherein the particle size distribution D90 / D10 of the multiple flat graphite particles is 2.0 to 4.4.

[0014] <3> The negative electrode material for lithium-ion secondary batteries as described in <2> has a particle size distribution D90 / D10 of 2.0 to 5.0.

[0015] <4> The negative electrode material for lithium-ion secondary batteries as described in any one of <1> to <3>, wherein the specific surface area of ​​the above-mentioned composite particles, determined by nitrogen adsorption measurement at 77K, is 0.5 m². 2 / g~2.8m 2 / g.

[0016] <5> The negative electrode material for lithium-ion secondary batteries as described in any one of <1> to <4> has a graphitization degree of 93.0% to 98.0% as determined by X-ray diffraction.

[0017] <6> The negative electrode material for lithium-ion secondary batteries as described in any one of <1> to <5>, wherein the intensity ratio (P1 / P2) of the diffraction peak (P1) of the rhombohedral structure (101) plane and the diffraction peak (P2) of the hexagonal crystal structure (101) plane in the X-ray diffraction pattern based on CuKα rays is less than or equal to 0.15.

[0018] <7> The negative electrode material for lithium-ion secondary batteries as described in any one of <1> to <6>, wherein the composite particles are composite particles on which at least a portion of the surface is disposed, and the R value of the composite particles disposed with low crystalline carbon is less than or equal to 0.50 as determined by Raman spectroscopy.

[0019] <8> The negative electrode material for lithium-ion secondary batteries as described in any one of <1> to <6>, wherein the composite particles are composite particles on which low-crystallinity carbon is not disposed on the surface, and the R value of the composite particles without low-crystallinity carbon is less than or equal to 0.20 as determined by Raman spectroscopy.

[0020] <9> The negative electrode material for lithium-ion secondary batteries as described in any one of <1> to <8>, wherein the oil absorption capacity of the composite particles is 15 mL / 100g to 45 mL / 100g.

[0021] <10> The negative electrode material for lithium-ion secondary batteries as described in any one of <1> to <9>, wherein the composite particles are compressed to a density of 1.8 g / cm³. 3 The pressure was then released, and the density was 1.8 g / cm³. 3 The absolute value of the density difference between the composite particles after pressure release and the density of the composite particles divided by the density 1.8 g / cm³ 3 The calculated rebound rate is greater than or equal to 40%.

[0022] <11> A negative electrode for a lithium-ion secondary battery, comprising a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises any one of <1> to <10> for a lithium-ion secondary battery.

[0023] <12> A lithium-ion secondary battery comprising the negative electrode, positive electrode and electrolyte described in <11> for a lithium-ion secondary battery.

[0024] <13> A method for manufacturing a negative electrode material for lithium-ion secondary batteries, comprising:

[0025] The process of classifying multiple flat, graphitizable aggregates and removing at least one selected from the group consisting of fine and coarse particles;

[0026] The process of mixing the graded, flat, graphitizable aggregates with a binder to obtain a mixture;

[0027] A process of processing the above mixture to produce secondary particles having a structure formed by stacking multiple flat, graphitizable aggregates.

[0028] The process of graphitizing the above-mentioned secondary particles to obtain composite particles having a structure composed of multiple stacked flat graphite particles; and

[0029] The process of classifying the above-mentioned composite particles to remove at least one of the group consisting of fine particles and coarse particles.

[0030] <14> The method for manufacturing a negative electrode material for lithium-ion secondary batteries as described in <13>, wherein the negative electrode material for lithium-ion secondary batteries is any one of <1> to <10>.

[0031] <15> In the method for manufacturing negative electrode material for lithium-ion secondary batteries as described in <13> or <14>, the particle size distribution D90 / D10 of the flat graphitizable aggregate is 2.0 to 4.4.

[0032] <16> In the method for manufacturing a negative electrode material for a lithium-ion secondary battery as described in any one of <13> to <15>, the bulk density of the graphitized secondary particles is 0.4 g / cm³. 3 ~1.0g / cm 3 .

[0033] <17> A method for manufacturing a negative electrode material for a lithium-ion secondary battery as described in any one of <13> to <16>, wherein processing of the mixture comprises heating the mixture to volatilize the volatile components of the binder.

[0034] <18> The method for manufacturing a negative electrode material for lithium-ion secondary batteries as described in <17> includes reducing the pressure in the atmosphere during the above heating process.

[0035] Invention Effects

[0036] According to this disclosure, a negative electrode material for a lithium-ion secondary battery, capable of producing a lithium-ion secondary battery with excellent high-temperature resistance and excellent electrolyte injection properties, and a method for manufacturing the same, as well as a negative electrode for a lithium-ion secondary battery and a lithium-ion secondary battery made using the negative electrode material, are provided. Attached Figure Description

[0037] [ Figure 1A [Image showing an electron microscope photograph of the negative electrode material in Example 1]

[0038] [ Figure 1B [Image showing an electron microscope photograph of the cross-section of the negative electrode material in Example 1.]

[0039] [ Figure 2A [Image shows an electron microscope photograph of the negative electrode material of Comparative Example 1.]

[0040] [ Figure 2B [Image shows an electron microscope photograph of the cross-section of the negative electrode material in Comparative Example 1.]

[0041] [ Figure 3A [Image shows an electron microscope photograph of the negative electrode material of Comparative Example 2.]

[0042] [ Figure 3B [Image shows an electron microscope photograph of the cross-section of the negative electrode material in Comparative Example 2.]

[0043] [ Figure 4A [Image shows an electron microscope photograph of the negative electrode material of Comparative Example 3.]

[0044] [ Figure 4B [Image shows an electron microscope photograph of the cross-section of the negative electrode material in Comparative Example 3.] Detailed Implementation

[0045] The following describes in detail the methods for implementing the present invention. However, the present invention is not limited to the following embodiments. In the following embodiments, the constituent elements (including element steps, etc.) are not essential unless specifically stated otherwise. Similarly, numerical values ​​and their ranges are not intended to limit the present invention.

[0046] In this disclosure, the term "process" includes not only processes that are independent of other processes, but also processes that can achieve their purpose, even when they cannot be clearly distinguished from other processes.

[0047] In this disclosure, the numerical range represented by “~” includes the minimum and maximum values ​​recorded before and after “~”, respectively.

[0048] In the numerical ranges described in this disclosure, the upper or lower limit of one numerical range can be replaced with the upper or lower limit of another numerical range described in other stages. Furthermore, the upper or lower limit of the numerical ranges described in this disclosure can be replaced with the values ​​shown in the embodiments.

[0049] In this disclosure, each component may contain multiple corresponding substances. When multiple substances equivalent to each component are present in the composition, unless otherwise specified, the content or percentage of each component refers to the total content or percentage of the multiple substances present in the composition.

[0050] In this disclosure, the particles corresponding to each component may include multiple types. When multiple particles corresponding to each component are present in the composition, unless otherwise specified, the particle size of each component refers to a value for a mixture of the multiple particles present in the composition.

[0051] In this disclosure, the term "layer" or "film" includes, in addition to the case where it is formed in the entire region when the region where the layer or film is observed, the case where it is formed only in a part of the region.

[0052] In this disclosure, the term "layering" refers to stacking layers, which can involve combining two or more layers or having two or more layers that are detachable.

[0053] In this disclosure, the particle size distribution of primary particles contained in the negative electrode material and composite particles can be determined using a laser diffraction particle size distribution measuring device. The average particle size is the particle size (D50) at which the cumulative particle size distribution from the small diameter side reaches 50% in a volume-based particle size distribution. D90 is the particle size at which the cumulative particle size distribution from the small diameter side reaches 90% in a volume-based particle size distribution, and D10 is the particle size at which the cumulative particle size distribution from the small diameter side reaches 10% in a volume-based particle size distribution.

[0054] Negative electrode materials for lithium-ion secondary batteries

[0055] The negative electrode material for lithium-ion secondary batteries in the first embodiment of this disclosure comprises composite particles having a structure formed by stacking multiple flat graphite particles, wherein the particle size distribution D90 / D10 of the composite particles is 2.0 to 5.0.

[0056] According to the negative electrode material of the first embodiment of this disclosure, it is possible to manufacture a lithium-ion secondary battery with excellent high-temperature resistance and excellent electrolyte injection properties. While the reasons may not be immediately clear, it can be considered as follows: The negative electrode material of the first embodiment of this disclosure comprises specific composite particles having a structure formed by stacking multiple flat graphite particles. It is believed that, through this stacked structure, when manufacturing the negative electrode material, compared to, for example, the negative electrode material described in International Publication No. 2015 / 147012, the interface between the specific composite particles and the electrolyte can be reduced, and electrolyte decomposition can be suppressed even at high temperatures. Furthermore, it is believed that, by having this stacked structure, even under pressure during negative electrode manufacturing, the particles are not easily crushed, and the electrolyte flow is not easily obstructed. Therefore, it is believed that electrolyte injection properties can be well maintained. Further, in the negative electrode material of the first embodiment of this disclosure, the particle size distribution D90 / D10 of the specific composite particles is 2.0 to 5.0. It is believed that although the number of fine pores inside specific composite particles is small, the particle size distribution D90 / D10 of specific composite particles is 2.0 to 5.0, and the particle size deviation is small. Therefore, the passage of electrolyte can be well maintained through the gaps between particles.

[0057] The negative electrode material for lithium-ion secondary batteries according to the second embodiment of this disclosure comprises composite particles having a structure formed by stacking multiple flat graphite particles, wherein the particle size distribution D90 / D10 of the multiple flat graphite particles is 2.0 to 4.4.

[0058] According to the negative electrode material of the second embodiment of this disclosure, it is possible to manufacture a lithium-ion secondary battery with excellent high-temperature resistance and excellent electrolyte injection properties. While the reasons may not be immediately clear, it can be considered as follows: The negative electrode material of the second embodiment of this disclosure comprises specific composite particles having a structure formed by stacking multiple flat graphite particles. It is believed that, through this stacked structure, when manufacturing the negative electrode material, for example compared to the negative electrode material described in International Publication No. 2015 / 147012, the interface between the specific composite particles and the electrolyte can be reduced, and electrolyte decomposition can be suppressed even at high temperatures. Furthermore, it is believed that, by having this stacked structure, even under pressure during negative electrode manufacturing, the particles are not easily crushed, and the electrolyte flow is not easily obstructed. Therefore, it is believed that electrolyte injection properties can be well maintained. In addition, in the negative electrode material of the second embodiment of this disclosure, the particle size distribution D90 / D10 of the multiple flat graphite particles (i.e., primary particles) is 2.0 to 4.4. It is believed that because the multiple flat graphite particles have a relatively uniform particle size, they can appropriately form a stacked structure, reducing the amount of pores within the composite particles and thus decreasing the specific surface area. Therefore, it is thought that this can suppress electrolyte decomposition and achieve superior high-temperature resistance. Furthermore, since particles with a more orderly stacked structure, higher hardness, and thus elasticity can be obtained, it is believed that even under pressure during negative electrode fabrication, the particle shape easily recovers, i.e., they are prone to rebound. As a result, it is believed that the electrolyte flow path can be well maintained during battery fabrication, further improving electrolyte injection performance.

[0059] Hereinafter, the negative electrode materials for lithium-ion secondary batteries in the first and second embodiments of this disclosure will sometimes be referred to as "the negative electrode materials of this disclosure" or "negative electrode materials".

[0060] In addition, composite particles with a structure consisting of multiple flat graphite particles stacked together are sometimes referred to as "specific composite particles".

[0061] It should be noted that the negative electrode material for lithium-ion secondary batteries disclosed herein has been found to suppress the deposition of metallic lithium at the negative electrode during charging. While the reason is unclear, one possible explanation is that, by maintaining the electrolyte pathway effectively, lithium ions do not remain at the negative electrode but readily migrate towards the positive electrode.

[0062] The negative electrode material disclosed herein may or may not contain particles other than the specific composite particles. That is, the negative electrode material disclosed herein may consist substantially only of the specific composite particles, or it may be a mixture of the specific composite particles and other particles. Here, "consistently consisting substantially only of the specific composite particles" means that even if a small amount of particles other than the specific composite particles are mixed in the negative electrode material (e.g., less than or equal to 5% by mass of the total negative electrode material, preferably less than or equal to 3% by mass), it is to a degree that does not practically affect the battery characteristics.

[0063] As particles other than specific composite particles, examples include negative electrode materials and conductive additives.

[0064] Examples of anode materials other than specific composite particles include natural graphite, artificial graphite, amorphous coated graphite, resin-coated graphite, amorphous carbon, and metal-encapsulated particles.

[0065] Examples of conductive additives include carbon black, graphite, acetylene black, conductive oxides, and conductive nitrides.

[0066] When the negative electrode material is a mixture of specific composite particles and particles other than the specific composite particles, the proportion of the specific composite particles relative to the total amount of the negative electrode material can be greater than or equal to 50% by mass, greater than or equal to 60% by mass, greater than or equal to 70% by mass, greater than or equal to 80% by mass, or greater than or equal to 90% by mass. Furthermore, the proportion of the specific composite particles relative to the total amount of the negative electrode material can be less than or equal to 90% by mass.

[0067] [Specific composite particles]

[0068] Certain composite particles have a structure consisting of multiple flat graphite particles stacked (i.e., piled up).

[0069] Flat graphite particles refer to non-spherical graphite particles with anisotropic shapes. Examples of flat graphite particles include those with scaly, flake-like, and partially blocky shapes.

[0070] A composite particle is a particle that is a collection or combination of primary particles. Specifically, a particular composite particle has a structure formed by the superposition or combination of multiple flat graphite particles with their main faces facing each other. Therefore, multiple flat graphite particles superimposed in a roughly parallel state form a composite particle. Whether the flat graphite particles are stacked can be confirmed by microscopic observation.

[0071] The state of multiple flat graphite particles aggregated or combined refers to the state of two or more flat graphite particles aggregated or combined. Combination refers to the state in which particles are chemically bonded to each other directly or through carbon materials. In addition, aggregation refers to the state in which particles are not chemically bonded to each other, but maintain the shape of an aggregate due to their shape and other reasons.

[0072] Flat graphite particles can aggregate or bond together with carbonaceous materials. Examples of carbonaceous materials include graphite obtained by graphitizing organic binders such as tar and pitch. Whether flat graphite particles have aggregated or bonded can be confirmed, for example, by observation using a scanning electron microscope.

[0073] There are no particular limitations on the flat graphite particles and their raw materials, and examples include artificial graphite, flake natural graphite, flaky natural graphite, coke, and resin. Among these, artificial graphite is preferred from the viewpoint of being less prone to deformation and having a low specific surface area. When using natural graphite as part of the raw material, from the viewpoint of being less prone to spheroidization and easier to obtain layered structures, the proportion of natural graphite in a specific composite particle is preferably less than or equal to 40% by mass.

[0074] From the viewpoint of ease of assembly or combination, the average particle size of the flat graphite particles constituting the specific composite particles is preferably 5 μm to 25 μm, more preferably 8 μm to 20 μm, and even more preferably 10 μm to 15 μm.

[0075] The average particle size of flat graphite particles can be obtained by any of the following methods.

[0076] The average particle size of the flat, graphitizable aggregate described later as the raw material for a specific composite particle, i.e., the particle size (D50) at which the cumulative size from the small diameter side in the volumetric particle size distribution reaches 50%, can be regarded as the average particle size of the flat graphite particles constituting the specific composite particle.

[0077] Furthermore, the average particle size of the flattened graphite particles can be obtained by observing the cross-section of a specific composite particle using a scanning microscope and using it as the median value of the particle sizes of any 100 flattened graphite particles. In this case, the particle size of each flattened graphite particle is set as the diameter of a circle with the same area as the projected area, i.e., the equivalent diameter of the circle.

[0078] The particle size distribution D90 / D10 of the flat graphite particles is preferably less than or equal to 4.4, more preferably less than or equal to 4.0, and even more preferably less than or equal to 3.5. If the particle size distribution D90 / D10 of the flat graphite particles is less than or equal to 4.4, it tends to have improved high-temperature resistance and liquid injection properties. From the viewpoint of reducing manufacturing costs, the particle size distribution D90 / D10 of the flat graphite particles can be greater than or equal to 2.0. From the above viewpoints, the particle size distribution D90 / D10 of the flat graphite particles is preferably 2.0 to 4.4, more preferably 2.0 to 4.0, and even more preferably 2.0 to 3.5.

[0079] It should be noted that in the negative electrode material involved in the second embodiment, the particle size distribution D90 / D10 of the flat graphite particles is 2.0 to 4.4.

[0080] The particle size distribution D90 / D10 of flat graphite particles can be obtained by any of the following methods.

[0081] The particle size distribution D90 / D10 obtained by measuring the flat, graphitizable aggregate described later as a raw material for a specific composite particle using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation) can be regarded as the particle size distribution D90 / D10 of the flat graphite particles constituting the specific composite particle.

[0082] Furthermore, the particle size distribution D90 / D10 of the flattened graphite particles can be obtained by observing the cross-section of a specific composite particle using a scanning microscope and taking it as the ratio of the particle size (D90) when the cumulative number of any 1000 flattened graphite particles from the small diameter side reaches 90% to the particle size (D10) when the cumulative number from the small diameter side reaches 10%. In this case, the particle size of each flattened graphite particle is set as the diameter of a circle with the same area as the projected area, i.e., the equivalent diameter of the circle.

[0083] Regarding flat graphite particles, when the length along the major axis is denoted as A and the length along the minor axis as B, the aspect ratio expressed as A / B is preferably 2 to 20, more preferably 4 to 10. If the aspect ratio is greater than or equal to 2, the outer surface area increases further, thus tending to cause particle aggregation due to the reduced buoyancy. When particles aggregate, the outer surface area decreases by stacking surfaces with long axes, resulting in a maximum adhesion area between particles. Combined with the van der Waals forces acting between particles, this leads to stronger adhesion and stabilization. If the aspect ratio is less than or equal to 20, there is a tendency to further improve input / output characteristics such as the rapid charge / discharge characteristics of lithium-ion secondary batteries. Furthermore, if the aspect ratio is less than or equal to 20, each flat graphite particle becomes thinner, the number of layers increases, the interparticle spacing increases, and the specific surface area increases, resulting in the ability to suppress the decrease in retention characteristics.

[0084] Aspect ratio is determined by observing graphite particles under a microscope. One hundred graphite particles are randomly selected, and their A / B ratios are measured. The arithmetic mean of these measurements is then taken. When observing the aspect ratio, the length A along the major axis and the length B along the minor axis are measured as follows: In the projected image of the graphite particles observed under a microscope, the tangent a1 and a2, which are parallel to and tangent to the outer periphery of the graphite particle, are selected. The distance between these two tangents is defined as the length A along the major axis. Similarly, the distance between these two tangents b1 and b2, which are parallel to and tangent to the outer periphery of the graphite particle, is selected. The distance between these two tangents is defined as the length B along the minor axis.

[0085] Certain composite particles may have low-crystallinity carbon configured on at least a portion of their surface. If low-crystallinity carbon is configured on at least a portion of the surface of a particular composite particle, there is a tendency for improved charging characteristics at low temperatures when constructing a lithium-ion secondary battery.

[0086] On the other hand, specific composite particles may not require the formation of low-crystallinity carbon on their surface. If low-crystallinity carbon is not formed on the surface of the specific composite particles, there is a tendency to suppress cracking and peeling of the specific composite particles during electrode fabrication under pressure, thereby inhibiting the electrolyte from decomposing and reducing storage properties. Furthermore, this provides the advantage of increased freedom in manufacturing conditions. According to the negative electrode material disclosed herein, it has been found that even without low-crystallinity carbon on the surface, it exhibits excellent rapid input / output characteristics. This is believed to be because, compared to the surface structure of the specific composite particles, liquid circulation (i.e., the diffusion rate of solvated lithium) has a greater impact on rapid input / output characteristics.

[0087] "Low-crystallinity carbon" refers to carbon with an R value greater than or equal to 0.2 in Raman spectra.

[0088] It should be noted that the R value is used in laser Raman spectroscopy measurements with an excitation wavelength of 532 nm, where 1360 cm⁻¹ is used. -1 Let the intensity of the largest peak appearing nearby be Id, and set 1580cm. -1 When the intensity of the largest peak appearing nearby is set as Ig, the value is represented by the intensity ratio of these two peaks, Id / Ig.

[0089] 1360cm -1 The peaks appearing nearby are those typically identified as corresponding to the amorphous structure of carbon, for example, at 1300 cm⁻¹. -1 ~1400cm -1 The observed peak. Additionally, 1580cm. -1 The peaks that appear nearby are those that are typically identified as corresponding to the crystal structure of graphite, for example, at 1530 cm⁻¹. -1 ~1630cm -1 The observed peak.

[0090] In the determination of the R value, a Raman spectroscopy apparatus (e.g., NSR-1000 model manufactured by Nippon Spectroscopy Corporation) was used, and the obtained spectrum was performed with the following range as a baseline and under the following conditions.

[0091] Laser wavelength: 532nm

[0092] • Irradiation intensity: 1.5mW (measured by laser power monitor)

[0093] • Measurement range: 830cm -1 ~1940cm -1

[0094] • Irradiation time: 60 seconds

[0095] • Irradiation area: 4μm 2

[0096] Baseline: 1050cm -1 ~1750cm -1

[0097] (Average particle size)

[0098] From the viewpoint of further improving the permeability of the electrolyte, the average particle size of the specific composite particles is preferably 5 μm to 30 μm, more preferably 10 μm to 25 μm, and even more preferably 12 μm to 20 μm.

[0099] The average particle size of a specific composite particle can be determined using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation). The average particle size is the particle size (D50) that accumulates to 50% from the smallest diameter side in the particle size distribution on a volume basis.

[0100] Examples of methods for determining the average particle size of specific composite particles when manufacturing an electrode (negative electrode) using the negative electrode material disclosed herein include: fabricating a sample electrode, embedding the electrode in epoxy resin, mirror polishing it, and observing the electrode cross-section using a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"); and fabricating the electrode cross-section using an ion milling apparatus (e.g., Hitachi High Technology Corporation, "E-3500") and measuring it using a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"). In these cases, the average particle size is the median value of the particle sizes of 100 randomly selected particles from the specific composite particles.

[0101] (Particle size distribution D90 / D10)

[0102] The particle size distribution D90 / D10 of the specific composite particles in the negative electrode material is preferably less than or equal to 5.0, more preferably less than or equal to 4.0, and even more preferably less than or equal to 3.0. It is believed that if the particle size distribution D90 / D10 of the specific composite particles is less than or equal to 5.0, the electrolyte flow path can be maintained well, and the electrolyte injection performance can be maintained well.

[0103] The particle size distribution D90 / D10 of a specific composite particle can be greater than or equal to 2.0.

[0104] Based on the above viewpoint, the particle size distribution D90 / D10 of the specific composite particles is preferably 2.0 to 5.0, more preferably 2.0 to 4.0, and even more preferably 2.0 to 3.0.

[0105] It should be noted that, in the first embodiment, the particle size distribution D90 / D10 of the specific composite particles in the negative electrode material is 2.0 to 5.0.

[0106] Particle size distribution D90 / D10 can be measured using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation).

[0107] Examples of methods for determining the particle size distribution D90 / D10 of specific composite particles when manufacturing an electrode (negative electrode) using the negative electrode material disclosed herein include: fabricating a sample electrode, embedding the electrode in epoxy resin, mirror polishing it, and observing the electrode cross-section using a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"); and fabricating the electrode cross-section using an ion milling apparatus (e.g., Hitachi High Technology Corporation, "E-3500") and measuring it using a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"). The particle size distribution D90 / D10 can then be obtained using the following methods.

[0108] (1) Use binarization method to find the area Sn of the mapped particle (n is the inherent number of the selected particle).

[0109] (2) Assuming the particle is an ideally shaped sphere, the equivalent diameter of the circle is calculated from the area Sn.

[0110] (3) Calculate the volume of the sphere Vn = (4 / 3)π(Ln) from the equivalent diameter of the circle Ln. 3 .

[0111] (4) Repeat (1) to (3) for the selected 100 particles.

[0112] (5) Set the vertical axis to the cumulative percentage of the volume of 100 quantities, the horizontal axis to the particle size distribution curve, the particle size at the point where the curve intersects the horizontal axis of 10% is set to the 10% diameter (D10), and the particle size at the point where the curve intersects the horizontal axis of 90% is set to the 90% diameter (D90), so that D90 / D10 can be calculated.

[0113] (Standard deviation of particle size distribution)

[0114] The standard deviation of the particle size distribution of specific composite particles in the negative electrode material is preferably less than or equal to 0.30, more preferably less than or equal to 0.25, and even more preferably less than or equal to 0.20. It is believed that if the standard deviation of the particle size distribution is less than or equal to 0.30, the electrolyte flow path and electrolyte injection properties can be well maintained. There is no particular limitation on the lower limit of the standard deviation of the particle size distribution. The standard deviation of the particle size distribution can be determined using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation) based on a frequency distribution curve with the horizontal axis set to a logarithmic scale of particle size and the vertical axis set to particle quantity (%).

[0115] (Specific surface area)

[0116] The specific surface area (N2 specific surface area) of the specific composite particles, determined by nitrogen adsorption at 77 K, is preferably 0.5 m².2 / g~2.8m 2 / g, more preferably 0.5m 2 / g~2.4m 2 / g, further preferably 0.5m 2 / g~2.2m 2 / g, preferably greater than or equal to 0.5m 2 / g and less than 2.0m 2 / g. If the specific surface area is greater than or equal to 0.5m² 2 If the specific surface area is less than or equal to 2.8 m² / g, the current density per unit area will not increase abruptly, thus suppressing the load and exhibiting a tendency to improve rapid charge and discharge efficiency. 2 If the ratio is / g, the interface between the electrolyte and the electrolyte will not become too large, thus inhibiting the decomposition of the electrolyte, and therefore tends to achieve better high-temperature resistance.

[0117] The specific surface area of ​​N2 can be determined using the BET method based on the adsorption isotherm obtained by measuring nitrogen adsorption at 77 K. Specifically, the specific surface area can be determined using the method described in the examples.

[0118] (oil absorption)

[0119] The oil absorption capacity of the specific composite particles is preferably 10mL / 100g to 60mL / 100g, more preferably 15mL / 100g to 45mL / 100g, and even more preferably 20mL / 100g to 40mL / 100g.

[0120] An oil absorption rate of 45 mL / 100 g or less is considered to indicate a low amount of micropores present within and on the particle surface. This suggests a smaller interface with the electrolyte, which improves storage properties. Furthermore, the smaller interface allows for a reduction in the amount of binder used in the fabrication of the negative electrode, thus tending to lower resistance and improve battery performance. Additionally, fewer micropores reduce the amount of solvent used during electrode drying, which is advantageous in terms of cost and environmental impact regarding drying equipment and production lines for power suppression.

[0121] If the oil absorption is greater than or equal to 10 mL / 100 g, it tends to suppress the increase in slurry viscosity during mixing with binders due to the small interparticle gaps. Furthermore, it tends to facilitate proper spreading of binders and easy mixing. Additionally, it easily ensures sufficient interparticle gaps for lithium ion movement.

[0122] In this disclosure, the oil absorption can be determined using linseed oil (e.g., manufactured by Kanto Chemical Co., Ltd.) instead of dibutyl phthalate (DBP) as the reagent liquid described in JIS K6217-4:2017 "Carbon black for rubber - basic properties - Part 4: method for determining oil absorption". Specifically, linseed oil is added dropwise to the target powder using a constant-speed burette, and the change in viscosity characteristics is measured by a torque detector. The amount of linseed oil added per unit mass of the target powder, corresponding to 70% of the maximum torque produced, is defined as the oil absorption (mL / 100g). As the measuring instrument, for example, an absorption measuring device (trade name: S-500) from ASAHISOUKEN Co., Ltd. can be used. Specifically, the oil absorption can be obtained using the method described in the examples.

[0123] (Saturated tap density)

[0124] There are no particular limitations on the saturated tap density of specific composite particles, but it is preferably 0.80 g / cm³. 3 ~1.60g / cm 3 More preferably 0.90 g / cm³ 3 ~1.50g / cm 3 Further preferred is 1.00 g / cm³ 3 ~1.40g / cm 3 .

[0125] Saturated tap density is an indicator of the high density of the negative electrode. If the saturated tap density is greater than or equal to 0.80 g / cm³... 3 This further enhances the compressibility during negative electrode formation, leading to higher electrode density and a tendency to obtain higher-capacity lithium-ion secondary batteries. If the saturated tap density is less than or equal to 1.60 g / cm³... 3 This tends to result in the appropriate existence of gaps between particles, further enhancing the permeability of the electrolyte and improving input-output characteristics such as rapid charge-discharge characteristics.

[0126] The saturated tap density of a specific composite particle can be determined using known methods. For example, in a volume of 150 cm⁻¹ 3 100 cm³ of sample powder was added to a graduated flat-bottomed test tube (e.g., KRS-406 manufactured by Kurumichi Scientific Instruments Co., Ltd.). 3 With the stopper in place, the sample is dropped from a height of 5 cm. The mass (g) and volume (cm³) of the powdery sample after the drop are measured. 3 The number of taps is sufficient to reach saturation density. Specifically, the saturation tap density can be obtained using the method described in the examples.

[0127] (Suppressing pressure)

[0128] In specific composite particles, the compressive pressure, as determined by the following method, is preferably greater than or equal to 2.1 kN / cm. 2 More preferably, greater than or equal to 2.4 kN / cm 2 Further preferred values ​​are greater than or equal to 2.7 kN / cm. 2 Compression pressure can be used as one of the hardness indicators for specific composite particles. If the compression pressure is greater than or equal to 2.1 kN / cm², it indicates a high hardness. 2 These composite particles have high hardness, and even when pressure is applied during the fabrication of the negative electrode, they tend to maintain the electrolyte flow well when the battery is made.

[0129] The pressing pressure can be less than or equal to 4.5 kN / cm. 2 It can be less than or equal to 4.3 kN / cm 2 It can also be less than or equal to 4.0 kN / cm 2 If the pressing pressure is less than or equal to 4.5 kN / cm 2 It exhibits the following tendencies: Because the hardness is not excessively high, it can suppress the pressing pressure during the fabrication of the negative electrode, preventing dimensional deviations or warping of the copper foil substrate due to rolling, which could lead to delamination at the interface between the active material and the current collector, resulting in reduced capacity and increased resistance. Furthermore, it has the following tendency: it can suppress the formation of crystal cracks in the active material due to excessive loading, or the increase of rhombohedral structures in the graphite crystal layer due to structural deviation, thereby reducing high-temperature storage characteristics.

[0130] Based on the above viewpoints, the preferred pressing pressure is 2.1 kN / cm. 2 ~4.5kN / cm 2 More preferably 2.4 kN / cm 2 ~4.3kN / cm 2 The optimal value is 2.7 kN / cm. 2 ~4.0kN / cm 2 .

[0131] The compression pressure was measured using the following method: 3.0 g of specific composite particles were filled into a mold with a diameter of 15 mm, and compression was performed at a constant speed of 10 mm / min using an Autograph (e.g., manufactured by Shimadzu Corporation). During compression, the distance from the bottom surface of the negative electrode material to the pressing surface was measured and multiplied by the bottom area of ​​the mold (e.g., 1.767 cm²). 2 The density under pressure is calculated from the volume of the resulting negative electrode material. Autograph's indenter is equipped with a load sensor to achieve a predetermined density of 1.8 g / cm³. 3 The applied pressure (kN / cm)2 The pressing pressure is set as the pressure. Specifically, the pressing pressure can be obtained using the method described in the embodiments.

[0132] (Rebound amount)

[0133] In a specific composite particle, the springback amount, as determined by the following method, is preferably greater than or equal to 40%, more preferably greater than or equal to 45%, and even more preferably greater than or equal to 50%. As an elasticity indicator of a specific composite particle, the higher the springback amount, the more elastic it is. Therefore, if the springback amount is greater than or equal to 40%, the specific composite material has moderate elasticity, and its shape easily recovers even under pressure when manufacturing the negative electrode, which is therefore preferred.

[0134] The rebound amount can be calculated as follows: compress the specific composite particles until the density of the specific composite particles reaches 1.8 g / cm³. 3 Then, the pressure is released, and the density is 1.8 g / cm³. 3 The absolute value of the density difference between the composite particles and the density after pressure release, divided by the density 1.8 g / cm³. 3 Thus, the result is obtained. Specifically, 3.0g of specific composite particles are filled into a mold with a diameter of 15mm, and the specific composite particles are compressed at a constant speed of 10mm / min using an Autograph (e.g., manufactured by Shimadzu Corporation) until the density of the specific composite particles reaches 1.8g / cm³. 3 (Baseline density). Then release the pressure, resulting in a density of 1.8 g / cm³. 3 The absolute value of the density difference between the composite particles after pressure release and the density of the composite particles divided by the density 1.8 g / cm³ 3 Therefore, it can be obtained. Specifically, the rebound amount can be obtained using the method described in the embodiments.

[0135] (Peak intensity ratio of rhombohedral structure)

[0136] In a specific composite particle, the intensity ratio (P1 / P2, also known as the rhombohedral structure peak intensity ratio) of the diffraction peak (P1) of the (101) plane of the rhombohedral structure and the diffraction peak (P2) of the (101) plane of the hexagonal crystal structure in an X-ray diffraction pattern based on CuKα rays can be less than or equal to 0.15, less than or equal to 0.10, or less than or equal to 0.05. The aforementioned peak intensity ratio (P1 / P2) is preferably within a range that cannot be observed by the methods described below. If the aforementioned peak intensity ratio (P1 / P2) is less than or equal to 0.15, there is a tendency for the negative electrode material for lithium-ion secondary batteries to have a higher degree of graphitization and a higher charge / discharge capacity.

[0137] The aforementioned peak intensity ratio of the rhombohedral structure can be calculated based on the intensity ratio of the diffraction lines of the rhombohedral structure (P1: diffraction angle 43.2°) to that of the hexagonal structure (P2: diffraction angle 44.3°) in an X-ray diffraction pattern using CuKα rays. Here, the diffraction angle is represented by 2θ (θ is the Bragg angle), with the (101) facet of the rhombohedral structure appearing at a diffraction angle of 43.2° and the (101) facet of the hexagonal structure appearing at a diffraction angle of 44.3°.

[0138] The peak intensity ratio of the above rhombohedral structure can be adjusted as follows: adjusting the degree of graphitization (e.g., adjusting the heat treatment temperature); graphitizing at a predetermined bulk density during the production of specific composite particles, forming without graphitization, and crushing after graphitization; or graphitizing after forming but crushing with a weaker force.

[0139] (degree of graphitization)

[0140] The degree of graphitization of the specific composite particles, determined by X-ray diffraction, is preferably greater than or equal to 93.0% and less than or equal to 98.0%, more preferably greater than or equal to 93.5% and less than or equal to 97.0%, and may also be greater than or equal to 94.0% and less than or equal to 96.0%. If the degree of graphitization is less than or equal to 98.0%, the specific composite particles tend to have higher hardness, resulting in particles that are elastic and not easily crushed even under pressure. Therefore, they tend to maintain the electrolyte's fillability more appropriately. If the degree of graphitization is greater than or equal to 93.0%, the discharge capacity tends to be excellent.

[0141] The degree of graphitization can be obtained, for example, as follows.

[0142] Sixty parts by mass of specific composite particles and 40 parts by mass of silicon powder (e.g., Fujifilm and Kojun Pharmaceutical Co., Ltd., 99.9% purity) were mixed in an agate mortar for 5 minutes, and the resulting mixture was placed in a sample cell for X-ray diffraction measurement. Using an X-ray diffraction apparatus (e.g., Rigaku X-ray diffraction apparatus, X-RAYDIFFRACTIOMETER MultiFlex), the diffraction angles corresponding to the (002) plane of graphite and the (111) plane of silicon were measured by X-ray diffraction measurement of CuKα rays (2θ = 25° to 29°).

[0143] The observed diffraction angles of silicon and graphite were corrected using the theoretical diffraction angle of Si (2θ = 28.442°), thereby obtaining the correct diffraction angle of graphite.

[0144] The interplanar spacing of the d(002) plane of the negative electrode material was calculated using Bragg's formula (2dsinθ=nλ). The degree of graphitization is calculated using the following formula.

[0145] Degree of graphitization = [(3.44 - interplanar spacing) / (0.086)] × 100

[0146] (average interface spacing (d) 002 ))

[0147] The average interplanar spacing (d) of a specific composite particle, determined by X-ray diffraction. 002 The average interplanar spacing (d) of graphite crystals is preferably greater than or equal to 0.33557 nm, more preferably greater than or equal to 0.33566 nm, and even more preferably greater than or equal to 0.33574 nm. 002 The theoretical value for ) is 0.3354 nm, and the closer it is to this value, the higher the degree of graphitization. Furthermore, if the average interplanar spacing (d) 002 If the particle size is greater than or equal to 0.33557 nm, then because the graphitization has not been excessive, it is a relatively hard particle, and therefore tends to maintain the electrolyte pathway well even when pressure is applied during the fabrication of the negative electrode.

[0148] From the perspective of the initial charge-discharge efficiency and energy density of lithium-ion secondary batteries, the average interplanar spacing (d 002 Preferably less than or equal to 0.33600 nm, more preferably less than or equal to 0.33596 nm, and even more preferably less than or equal to 0.33592 nm.

[0149] Based on the above viewpoints, the average interplanar spacing (d) 002 The preferred wavelength range is 0.33557nm to 0.33600nm, more preferably 0.33566nm to 0.33596nm, and even more preferably 0.33574nm to 0.33592nm.

[0150] Average inter-face spacing (d) 002 The average interplanar spacing (d) can be calculated as follows: Based on the diffraction pattern obtained by irradiating the sample with X-rays (CuKα rays) and measuring the diffraction lines using a goniometer, the average interplanar spacing (d) is calculated using Bragg's formula, using the diffraction peaks corresponding to the carbon 002 plane that appear around the diffraction angle 2θ reaches 24°–27°. 002 The following conditions can be met for determination.

[0151] Radiation source: CuKα rays (wavelength = 0.15418 nm)

[0152] Output: 40kV, 20mA

[0153] Sampling width: 0.010°

[0154] Scanning range: 10°~35°

[0155] Scanning speed: 0.5° / min

[0156] Bragg's formula: 2dsinθ=nλ

[0157] Where d represents the length of one period, θ represents the diffraction angle, n represents the number of reflections, and λ represents the X-ray wavelength.

[0158] The average interplanar spacing (d) of a specific composite particle 002 The value of ) tends to decrease, for example, by increasing the heat treatment temperature during the fabrication of composite particles and increasing the holding time. Therefore, by adjusting the heat treatment temperature and holding time during the fabrication of specific composite particles, the average interplanar spacing (d) can be controlled. 002 ).

[0159] (R value determined by Raman spectroscopy)

[0160] There are no particular limitations on the Raman-determined R value (hereinafter also referred to as R value) for a specific composite particle.

[0161] In one embodiment, when the specific composite particles are composite particles without low-crystallinity carbon disposed on the surface, the R value is preferably less than or equal to 0.20, and from the viewpoint of high durability, it is preferably less than or equal to 0.15, more preferably less than or equal to 0.10. Furthermore, the R value can be greater than or equal to 0.03, greater than or equal to 0.04, or greater than or equal to 0.05. If the R value is greater than or equal to 0.03, there is a tendency for lithium ions to easily insert into the graphite crystals, thereby improving charging characteristics; additionally, there is a tendency to suppress the formation of lithium dendrites.

[0162] In another approach, when the specific composite particles are composite particles with low-crystallinity carbon disposed on at least a portion of their surface, the R value is preferably less than or equal to 0.50. From the viewpoint of high-temperature durability, the R value is more preferably less than or equal to 0.40, and even more preferably less than or equal to 0.30. Furthermore, in this case, the R value can be in the range of 0.20 to 0.50, 0.20 to 0.40, or 0.20 to 0.30. If the R value is in the range of 0.20 to 0.50, it is easier to desolvate lithium ions, and there is a tendency for more lithium insertion ports and improved low-temperature charging characteristics.

[0163] Conventional methods using particles with low-crystallinity carbon deposited on the surface of spherical natural graphite, where the surface has a relatively large amount of internal space, result in the particles being easily crushed during pressing due to the compression of this internal space. This deformation causes cracking in the coating layer (i.e., the low-crystallinity carbon layer on the surface), easily exposing the graphite nucleus. On the other hand, in specific composite particles with less space between the primary particles, less space is compressed during pressing, reducing the likelihood of cracking in the coating layer. Therefore, the specific surface area of ​​the exposed particles is smaller, resulting in fewer interfaces with the electrolyte and thus reducing the impact of the electrolyte. When the specific composite particles are those with low-crystallinity carbon deposited on at least a portion of the surface, considering the increase in the R-value due to pressing, the R-value is preferably less than or equal to 0.30.

[0164] The R value determined by Raman spectroscopy can be obtained using the method described above.

[0165] In the case where the negative electrode material disclosed herein is a mixture of specific composite particles and particles other than the specific composite particles, the following parameters are specified for the specific composite particles: average particle size, particle size distribution D90 / D10, standard deviation of particle size distribution, specific surface area, oil absorption, saturated tap density, pressing pressure, springback, peak intensity ratio of rhombohedral structure, degree of graphitization, and average interplanar spacing (d). 002 The details of the R value measured by Raman spectroscopy can also be applied to the overall properties of the negative electrode material.

[0166] Manufacturing Methods of Anode Materials

[0167] In one embodiment, the method for manufacturing the negative electrode material of this disclosure includes, in sequence:

[0168] (A) A process of mixing multiple flat, graphitizable aggregates with a binder to obtain a mixture;

[0169] (B) A process of processing the above mixture to produce secondary particles having a structure formed by stacking multiple flat, graphitizable aggregates; and

[0170] (C) A process of graphitizing the above-mentioned secondary particles to obtain a composite particle (specific composite particle) having a structure composed of multiple flat graphite particles stacked together.

[0171] The negative electrode material for lithium-ion secondary batteries disclosed herein can be manufactured using the method for manufacturing negative electrode materials of this disclosure. For details regarding the negative electrode material manufactured using the method for manufacturing negative electrode materials of this disclosure, the matters described above concerning the negative electrode material for lithium-ion secondary batteries can be used.

[0172] In another embodiment, the method for manufacturing the negative electrode material may include a step prior to obtaining the mixture in step (A) by classifying a plurality of flat, graphitizable aggregates to remove at least one selected from the group consisting of fine particles and coarse particles. By removing fine particles by classifying the graphitizable aggregates before primary particle composite formation, a tendency to reduce specific surface area is suppressed, thereby enabling the dense formation of a layered structure of specific composite particles.

[0173] In another embodiment, the method for manufacturing the negative electrode material may include, after the step of obtaining the composite particles in step (C), a step of classifying the composite particles to remove at least one selected from the group consisting of fine and coarse particles. It is believed that by classifying specific composite particles, particle size deviations of specific composite particles can be suppressed, and the electrolyte flow can be maintained more effectively.

[0174] Therefore, in a preferred embodiment, the method for manufacturing the negative electrode material includes, in sequence:

[0175] (a) A process of classifying multiple flat, graphitizable aggregates as needed and removing at least one selected from the group consisting of fine and coarse particles;

[0176] (b) A process of mixing multiple flat, graphitizable aggregates with a binder to obtain a mixture;

[0177] (c) A process of processing the above mixture to produce secondary particles having a structure formed by stacking multiple flat, graphitizable aggregates.

[0178] (d) The process of graphitizing the above-mentioned secondary particles to obtain composite particles (specific composite particles) having a structure composed of multiple layers of flat graphite particles; and

[0179] (e) A process of removing at least one of the group consisting of microparticles and coarse particles, as needed, by classifying the above-mentioned composite particles.

[0180] It should be noted that in this disclosure, "microparticles" refers to particles with a diameter smaller than those recovered through grading, and "coarse particles" refers to particles with a diameter larger than those recovered through grading.

[0181] The following describes in detail the various steps that may be included in the manufacturing method of the negative electrode material of this disclosure.

[0182] (a) A process of classifying multiple flat, graphitizable aggregates and removing at least one selected from the group consisting of fine and coarse particles.

[0183] Multiple flat, graphitizable aggregates can be graded before composite formation to remove at least one selected from the group consisting of fine and coarse particles. By removing at least one selected from the group consisting of fine and coarse particles from the aggregates, there is a tendency to form a dense, layered structure in the composite particles, thereby suppressing the specific surface area. Through grading, the particle size distribution D90 / D10 of the multiple flat, graphitizable aggregates can be adjusted to the aforementioned range, for example, 2.0 to 4.4, preferably 2.0 to 4.0, and more preferably 2.0 to 3.5.

[0184] As graphitizable aggregates, there are no particular limitations on the shape of flat particles; examples include petroleum-based or coal-based cokes such as fluid coke, needle coke, and interlocking coke. For instance, needle coke, due to its high crystallinity, easily becomes flat and readily produces layered particles. Furthermore, due to its high crystallinity, needle coke particles are also large, making particle size control through crushing and classification easy. When it is desirable to obtain graphite with high charging characteristics and lower crystallinity, semi-needle or interlocking coke, which is closer to the interlocking system, can be used. In this case, since there is a tendency to generate fine and coarse powders, it is preferable to thoroughly remove fine and coarse powders through classification.

[0185] During classification, it is preferable to remove particles with a diameter of 1 μm or less, more preferably to remove particles with a diameter of 2 μm or less, and even more preferably to remove particles with a diameter of 3 μm or less.

[0186] Furthermore, during grading, it is preferable to remove coarse particles with a particle size greater than or equal to 60 μm, more preferably to remove coarse particles with a particle size greater than or equal to 50 μm, and even more preferably to remove coarse particles with a particle size greater than or equal to 40 μm. The removed coarse particles can be crushed and reused as raw materials.

[0187] There are no particular restrictions on the classification method. Examples include classification using sieves, classification using airflow centrifuges, and precision airflow classifiers that utilize the wall adhesion effect.

[0188] (b) The process of mixing multiple flat, graphitizable aggregates with a binder to obtain a mixture.

[0189] As an adhesive, a graphitizable adhesive is used. Examples of adhesives include coal-based, petroleum-based, and synthetic asphalt and tar, thermoplastic resins, and thermosetting resins.

[0190] In addition, graphitization catalysts, flowability enhancers, etc., can be added as needed.

[0191] Examples of graphitization catalysts include silicon, iron, nickel, titanium, boron, vanadium, aluminum, and their carbides, oxides, nitrides, mica clay minerals, etc.

[0192] The amount of graphitizing catalyst is not limited as long as the target material is available. From the viewpoint of avoiding excessive graphitization, it is preferable to omit the graphitizing catalyst or reduce its amount. For example, when the graphitizing catalyst is silicon carbide (SiC), the content of silicon carbide relative to the mass of the graphitizable aggregate is preferably less than or equal to 5% by mass, and more preferably less than or equal to 3% by mass.

[0193] There are no particular limitations on the mixing method. From the viewpoint of reducing the amount of fine pores in secondary particles, a mixing method that applies as little shear force as possible is preferred, such as using an impact mixer or a paddle mixer. It is preferable not to use kneading machines or similar equipment that involve kneading, also known as mixing machines.

[0194] (c) A process of processing a mixture to produce secondary particles having a structure consisting of multiple flat, graphitizable aggregate layers.

[0195] There are no particular limitations on the processing method of the mixture. In one embodiment, processing can be carried out by heating the mixture to volatilize the volatile components of the binder. The heating temperature is preferably less than or equal to 400°C. If the heating temperature is less than or equal to 400°C, it is less likely to produce fine pores due to oxidation and combustion, and particles with a small specific surface area are easily obtained. In this case, by using a mixer or the like to heat the mixture while it is flowing, granulation can be easily and appropriately achieved.

[0196] When the mixture is heated, the atmosphere can be depressurized. By depressurizing the atmosphere, the binder can be easily impregnated into graphitizable aggregates, the gaps within the particles can be easily filled, and the stacked particles can be easily obtained with few internal pores.

[0197] The following is a specific example illustrating the method for producing secondary particles.

[0198] The mixture of graphitizable aggregate and binder is stirred for a period of time in a temperature range greater than or equal to the softening point of the binder, preferably in a temperature range where volatile components volatilize, until the volatile components are removed. By slowly degassing before graphitization (firing), there is a tendency for less bubble generation during crystallization sintering, resulting in particles with fewer pores within and on the particle surface, and a hard structure with low specific surface area and excellent high-temperature resistance. In this case, if an inactive gas such as nitrogen is introduced into the mixer to suppress the oxygen concentration to less than or equal to 15% to prevent ignition of the volatile gases, safety is excellent, and this is preferred. Furthermore, if the temperature inside the mixer is less than or equal to 400°C, it is less likely to generate fine pores due to oxidative combustion, and particles with small specific surface area are easily obtained, which is also preferred. Furthermore, when using bitumen as a binder, oxygen in the atmosphere can enter the bitumen, preventing it from melting. As a result, crystal growth during graphitization becomes better, and denser, higher-density crystals can be obtained.

[0199] If degassing, non-melting, and depressurization are performed in an environment where the binder components have softened and are in a liquid or gas phase with guaranteed flowability, there is a tendency to obtain higher results.

[0200] [(d) The process of graphitizing secondary particles to obtain composite particles (specific composite particles) having a structure composed of multiple layers of flat graphite particles]

[0201] In this process, the resulting secondary particles are graphitized. Thus, the graphitizable components in the secondary particles are graphitized. Graphitization is preferably carried out in an atmosphere where the mixture is not easily oxidized; for example, heating in a nitrogen atmosphere or argon atmosphere is an example. The graphitization temperature is not particularly limited as long as it is sufficient to graphitize the graphitizable components. For example, it can be greater than or equal to 2000°C, greater than or equal to 2500°C, greater than or equal to 2800°C, or greater than or equal to 3000°C. The upper limit of the above temperatures is not particularly limited as long as graphite does not sublimate; for example, it can be less than or equal to 3200°C. If the above temperature is greater than or equal to 2000°C, crystallization occurs. If the above temperature is greater than or equal to 2500°C, graphite crystal growth becomes good; if it is greater than or equal to 2800°C, there is a tendency to grow high-capacity graphite crystals capable of absorbing more lithium ions, and the amount of graphitization catalyst remaining after calcination is small, thus suppressing the increase in ash content. In either case, there is a tendency for improved charge / discharge capacity and battery cycle characteristics. On the other hand, if the graphitization temperature is less than or equal to 3200°C, sublimation of some of the graphite can be suppressed.

[0202] In this process, the degree of graphitization can be adjusted to less than or equal to 98.0%, preferably less than or equal to 97.0%, and more preferably less than or equal to 96.0%.

[0203] The method for manufacturing the negative electrode material disclosed herein may include a step of molding secondary particles before graphitization and a step of pulverizing the molded material after graphitization. By molding the secondary particles, the bulk density is increased, thereby increasing the filling capacity of the graphitization furnace, improving energy efficiency, and enabling energy-saving graphitization. The molding method is not particularly limited; for example, the secondary particles can be placed in a container such as a mold and pressurized.

[0204] On the other hand, the manufacturing method of the negative electrode material disclosed herein preferably does not include the step of forming secondary particles before graphitization. Since the manufacturing method of the negative electrode material disclosed herein does not include the step of forming secondary particles before graphitization, it is also preferable not to include the step of crushing the formed body. Therefore, it is believed that the increase of rhombohedral crystals during forming and crushing processes, such as block forming, can be suppressed, and high-temperature resistance can be more appropriately improved.

[0205] The bulk density of the secondary particles supplied during graphitization (i.e., immediately before graphitization) is preferably 0.4 g / cm³. 3 ~1.0g / cm 3 More preferably 0.6 g / cm³ 3 ~1.0g / cm 3 Further preferred is 0.8 g / cm³ 3 ~1.0g / cm 3 If the bulk density of the secondary particles before graphitization is greater than or equal to 0.4 g / cm³ 3 If the particle size distribution is low, there are fewer voids within the particles, thus exhibiting a tendency to produce high-density composite particles even after graphitization. If the bulk density of the secondary particles before graphitization is less than or equal to 1.0 g / cm³, then... 3 It has the tendency to crush with weaker force during molding and crushing, and to suppress the increase of rhombohedral crystals.

[0206] In this disclosure, the bulk density of the particles can be obtained by gravimetric determination. That is, the bulk density of the particles can be determined by dividing the mass of the particles in air by their volumetric capacity. Here, the mass of the particles is set as the mass excluding the graphitization catalyst (for example, in the case of a mixture of aggregates, binders and graphitization catalyst, it is the total mass of the aggregates and binders after removing volatile components).

[0207] (e) A process of classifying composite particles to remove at least one selected from the group consisting of fine and coarse particles.

[0208] The resulting composite particles can be graded to remove at least one selected from the group consisting of microparticles and coarse particles. This is believed to make the particle size of the composite particles more uniform, thus better maintaining the electrolyte flow path. Through grading, the particle size distribution D90 / D10 of the composite particles can be adjusted to the aforementioned range, for example, 2.0 to 5.0, preferably 2.0 to 4.0, and more preferably 2.0 to 3.0.

[0209] There are no particular restrictions on the classification method. Examples include classification using sieves, classification using airflow centrifuges, and precision airflow classifiers that utilize the wall adhesion effect.

[0210] In this process, when removing particles, it is preferable to remove particles with a particle size of less than or equal to 1 μm, more preferably to remove particles with a particle size of less than or equal to 2 μm, and even more preferably to remove particles with a particle size of less than or equal to 3 μm.

[0211] In this process, when removing coarse particles, it is preferable to remove coarse particles with a particle size greater than or equal to 60 μm, more preferably to remove coarse particles with a particle size greater than or equal to 50 μm, and even more preferably to remove coarse particles with a particle size greater than or equal to 40 μm.

[0212] [Other processes]

[0213] The method for manufacturing the negative electrode material disclosed herein may include steps other than those described above.

[0214] For example, a method for manufacturing a negative electrode material may include a step of attaching an organic compound to the surface of secondary particles after graphitization and then performing heat treatment. By attaching the organic compound to the surface of the secondary particles and performing heat treatment, the organic compound attached to the surface is transformed into low-crystallinity carbon. This allows low-crystallinity carbon to be disposed on at least a portion of the surface of the composite particles.

[0215] There are no particular limitations on the methods for attaching organic compounds to the surface of secondary particles. For example, examples include: a wet method in which secondary particles are dispersed and mixed in a mixed solution in which an organic compound is dissolved or dispersed in a solvent, and then the solvent is removed for attachment; and a dry method in which mechanical energy is applied to a mixture of secondary particles and a solid organic compound for attachment.

[0216] There are no particular restrictions on organic compounds, as long as they are substances that can be transformed into low-crystallinity carbon (carbon precursors) through heat treatment. Examples include petroleum-based asphalt, naphthalene, anthracene, phenanthroline, coal tar, phenolic resins, and polyvinyl alcohol. Organic compounds can be used alone or in combination of two or more.

[0217] The heat treatment temperature for secondary particles with organic compounds adhering to their surface is not particularly limited as long as it is the temperature at which the organic compounds adhering to the surface of the secondary particles change into low-crystallinity carbon; for example, 400°C to 1500°C is preferred. The heat treatment is preferably carried out in an inert gas atmosphere, such as nitrogen.

[0218] It should be noted that, as mentioned above, the specific composite particles contained in the negative electrode material of this disclosure may not have low-crystallinity carbon configured on their surface. Therefore, the manufacturing method of the negative electrode material of this disclosure may not include the step of attaching organic compounds to the surface of secondary particles after graphitization and performing heat treatment.

[0219] Negative electrode for lithium-ion secondary batteries

[0220] The negative electrode for lithium-ion secondary batteries disclosed herein comprises a negative electrode material layer containing the negative electrode material for lithium-ion secondary batteries of this disclosure, and a current collector. In addition to the negative electrode material layer and current collector containing the negative electrode material for lithium-ion secondary batteries of this disclosure, the negative electrode for lithium-ion secondary batteries may also include other constituent elements as needed.

[0221] A negative electrode for a lithium-ion secondary battery can be manufactured, for example, as follows: A slurry-like negative electrode material composition for a lithium-ion secondary battery is prepared by mixing a negative electrode material for a lithium-ion secondary battery with a binder and a solvent; this composition is then coated onto a current collector to form a negative electrode material layer. Alternatively, the negative electrode material composition for a lithium-ion secondary battery can be molded into sheet or granular shapes and integrated with the current collector. Mixing can be performed using dispersion equipment such as a dispersing mixer or a planetary mixer.

[0222] There are no particular limitations on the binder used in the preparation of the negative electrode material composition for lithium-ion secondary batteries. Examples of binders include styrene-butadiene copolymer (SBR), methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, etc., as well as homopolymers or copolymers of ethylene unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, polyvinylidene fluoride, polyethylene oxide, polyepoxychlorohydrin, polyphosphazene, polyacrylonitrile, polymethacrylonitrile, etc., which are polymers with high ion conductivity. When the negative electrode material composition for lithium-ion secondary batteries includes a binder, the content of the binder is not particularly limited. For example, it can be 0.5 parts by weight to 20 parts by weight relative to 100 parts by weight of the total negative electrode material and binder for lithium-ion secondary batteries.

[0223] The negative electrode material composition for lithium-ion secondary batteries may contain a thickener. As a thickener, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid or its salts, oxidized starch, phosphorylated starch, casein, etc., can be used. When the negative electrode material composition for lithium-ion secondary batteries contains a thickener, the content of the thickener is not particularly limited. For example, it can be 0.1 parts by weight to 5 parts by weight relative to 100 parts by weight of the negative electrode material for lithium-ion secondary batteries.

[0224] The negative electrode material composition for lithium-ion secondary batteries may include conductive additives. Examples of conductive additives include carbon materials such as carbon black, graphite, and acetylene black, as well as inorganic compounds such as oxides and nitrides that exhibit conductivity. When the negative electrode material composition for lithium-ion secondary batteries includes conductive additives, the content of the conductive additives is not particularly limited. For example, it may be 0.5 to 15 parts by weight relative to 100 parts by weight of the negative electrode material for lithium-ion secondary batteries.

[0225] There are no particular restrictions on the material of the current collector; it can be selected from aluminum, copper, nickel, titanium, stainless steel, etc. There are also no particular restrictions on the state of the current collector; it can be selected from foil, perforated foil, mesh, etc. In addition, porous materials such as porous metals (foamed metals) and carbon paper can also be used as current collectors.

[0226] When coating a negative electrode material composition for lithium-ion secondary batteries onto a current collector to form a negative electrode material layer, there are no particular limitations on the method. Known methods such as metal mask printing, electrostatic coating, dip coating, spraying, roller coating, doctor blade coating, corner wheel coating, gravure coating, and screen printing can be used. After coating the negative electrode material composition onto the current collector, the solvent contained in the composition is removed by drying. Drying can be performed using, for example, a hot air dryer, an infrared dryer, or a combination of these devices. The negative electrode material layer can also be calendered if necessary. Calendering can be performed using a flatbed press, calendering rollers, or similar methods.

[0227] When integrating a lithium-ion secondary battery negative electrode material composition, formed into the shape of sheets or granules, with a current collector to form a negative electrode material layer, the integration method is not particularly limited. For example, it can be carried out by a roller, a flatbed press, or a combination of these methods. The pressure when integrating the lithium-ion secondary battery negative electrode material composition with the current collector is preferably, for example, in the range of 1 MPa to 200 MPa.

[0228] There are no particular limitations on the negative electrode density of the negative electrode material layer. For example, a density of 1.1 g / cm³ is preferred. 3 ~1.8g / cm 3 More preferably 1.1 g / cm³ 3~1.7g / cm 3 Further preferred value is 1.1 g / cm³. 3 ~1.6g / cm 3 By setting the negative electrode density to be greater than or equal to 1.1 g / cm³ 3 This gives it a tendency to increase capacitance while suppressing an increase in resistance, if set to be less than or equal to 1.8 g / cm³. 3 This gives it a tendency to suppress the reduction of input and loop characteristics.

[0229] Lithium-ion secondary batteries

[0230] The lithium-ion secondary battery disclosed herein includes a negative electrode, a positive electrode, and an electrolyte for use in lithium-ion secondary batteries.

[0231] Similar to the method for manufacturing the negative electrode described above, the positive electrode can be obtained by forming a layer of positive electrode material on the current collector. As the current collector, a current collector made of metals or alloys such as aluminum, titanium, and stainless steel in the form of foil, perforated foil, or mesh can be used.

[0232] There are no particular limitations on the cathode material used to form the cathode material layer. Examples of cathode materials include metal compounds (metal oxides, metal sulfides, etc.) and conductive polymer materials that can be doped or intercalated with lithium ions. More specifically, examples include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their composite oxides (LiCo... x Ni y Mn z O2, x+y+z=1), composite oxides containing added element M' (LiCo) a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel-type lithium manganese oxide (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 The cathode material can be a single metal compound or a combination of two or more materials, including VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, and polybenzoxene, and porous carbon.

[0233] There are no particular restrictions on the electrolyte; for example, an electrolyte made by dissolving lithium salt, which serves as the electrolyte, in a non-aqueous solvent (so-called organic electrolyte) can be used.

[0234] Examples of lithium salts include LiClO4, LiPF6, LiAsF6, LiBF4, and LiSO3CF3. A lithium salt can be a single type or two or more.

[0235] Examples of non-aqueous solvents include ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, propylene carbonate, butyl carbonate, vinylene carbonate, cyclopentanone, cyclohexylbenzene, sulfolane, propanesulfonate lactone, 3-methylsulfolane, 2,4-dimethylsulfolane, and 3-methyl-1,3- Examples of non-aqueous solvents include 2-oxazolidinone, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, ethyl butyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, trimethyl phosphate, and triethyl phosphate. Non-aqueous solvents can be a single solvent or two or more.

[0236] The state of the positive and negative electrodes in a lithium-ion secondary battery is not particularly limited. For example, the positive and negative electrodes, along with the separator disposed between them as needed, can be wound in a vortex shape, or they can be stacked in a planar shape.

[0237] There are no particular limitations on the separator; for example, it can be a non-woven fabric, cloth, microporous membrane, or a combination of these made of resin. Examples of resins include those primarily composed of polyolefins such as polyethylene and polypropylene. In lithium-ion secondary batteries where the positive and negative electrodes are not in direct contact, a separator may not be necessary.

[0238] There are no particular restrictions on the shape of lithium-ion secondary batteries. Examples include laminated batteries, paper batteries, button batteries, coin-shaped batteries, stacked batteries, cylindrical batteries, and prismatic batteries.

[0239] The lithium-ion secondary battery disclosed herein has suitable input characteristics, making it suitable as a high-capacity lithium-ion secondary battery for use in electric vehicles, power tools, energy storage devices, etc. In particular, the lithium-ion secondary battery disclosed herein exhibits excellent high-temperature resistance, thus making it suitable as a lithium-ion secondary battery for use in commercial vehicles such as buses and delivery vehicles.

[0240] Example

[0241] The present invention will now be described in detail through examples, but the present invention is not limited to these examples.

[0242] Fabrication or preparation of negative electrode materials

[0243] [Example 1]

[0244] Needle-shaped coke derived from petroleum, characterized by a sulfur content of less than or equal to 0.5% by mass, a nitrogen content of less than or equal to 0.5% by mass, a fixed carbon content of greater than or equal to 98% by mass, and a needle-like stripe pattern observed on the cross-section of the particles under a polarizing microscope, was selected and coarsely ground using a hammer mill. The coarsely ground material was then sieved using a 3mm sieve, and the sieved material was further sieved using a 1mm sieve to recover particles with a diameter of 1mm to 3mm. The resulting particles were then ground using a roller mill to obtain particles with an average diameter of 200μm.

[0245] Using a reverse jet mill, a crushing pressure of 6 kgf / cm² will be applied. 2 The resulting particles were pulverized, and the coarse powder portion was removed at a classifying speed of 900 rpm to obtain pulverized powder with a particle size D90 less than or equal to 23 μm. Next, a high-speed rotary air classifier was used to classify the particles with a particle size D10 greater than or equal to 7 μm, obtaining flat coke particles that can be graphitized as aggregate. The volumetric particle size distribution of the obtained flat coke particles was measured, confirming that D10 was 7 μm and D90 was 23 μm.

[0246] The obtained flat coke particles (90% by mass) and coal tar pitch (softening point 100℃~150℃, quinoline insoluble content less than or equal to 15% by mass, fixed carbon 55%~75% by mass) were uniformly mixed at room temperature to obtain a mixture. Next, the mixing container containing the mixture was heated to 300℃~400℃ and depressurized under a mixed gas flow of dry air and nitrogen. At this time, if the stirring blades inside the mixer are rotated to facilitate gas expulsion, the specific surface area tends to decrease. The endpoint of heating and stirring was determined by the phenomenon that the viscosity of the mixture decreases due to the volatilization of low molecular weight gases in the coal tar pitch; this was set as the point at which the current value of the stirring blades decreases and stabilizes, yielding a bulk density of 0.88 g / cm³. 3 Specific granulation particles.

[0247] Next, the granulated particles were loaded into a graphitization container and graphitized at 3100°C. Then, the resulting particles were sieved through a 300-mesh screen to obtain the flat particle composite particles 1 of Example 1.

[0248] [Example 2]

[0249] The classifying speed of the reverse jet mill was set to 1000 revolutions per minute (rpm) to remove the coarse powder portion. Then, a high-speed rotary airflow classifier was used to classify the particles with a particle size D10 of 5 μm and a D90 of 20 μm. Otherwise, the operation was the same as in Example 1 to obtain the composite particles 2 of Example 2.

[0250] [Example 3]

[0251] The classifying speed of the reverse jet mill was set to 750 revolutions per minute (rpm) to remove the coarse powder portion, thereby obtaining pulverized powder with a particle size D10 of 7 μm and a D90 of 30 μm. Otherwise, the same operation as in Example 2 was performed to obtain the composite particles 3 of Example 3.

[0252] [Comparative Example 1]

[0253] 55 parts by mass of embedded coke pulverized to an average particle size of 15 μm, 25 parts by mass of tar pitch binder with a softening point of 110 °C, and 20 parts by mass of SiC as a catalyst were kneaded in a heated kneader at 130 °C, above the binder's melting temperature, to obtain a mixture of flattened particles oriented in a random direction. The resulting mixture was then extruded to obtain a molded product. This molded product was then heated to a maximum temperature greater than or equal to 2500 °C to graphitize it. The resulting graphitized product was pulverized and sieved to obtain secondary graphite particles with an average particle size of 23.0 μm.

[0254] [Comparative Example 2]

[0255] Prepare spherical natural graphite with an average particle size of 17 μm.

[0256] [Comparative Example 3]

[0257] Similar to Example 1, needle-shaped coke was coarsely pulverized using a hammer mill. Then, it was subjected to friction pulverization using a roller mill to obtain a thin, flaky powder containing numerous micro and coarse particles. It was confirmed that the flattened particles had a D10 of 6 μm, a D90 of 55 μm, and a cumulative volume percentage of particles smaller than or equal to 3 μm greater than or equal to 3%, containing a large amount of micro powder (the cumulative volume percentage of particles smaller than or equal to 3 μm in Examples 1-3 was less than or equal to 0.1%). A mixture was obtained by uniformly mixing 90% by mass of the flattened coke particles and 10% by mass of coal tar pitch (softening point 100°C–150°C, quinoline-insoluble content less than or equal to 15% by mass, fixed carbon 55%–75% by mass) at room temperature. The mixture was then placed in a graphite container, covered, and calcined at 1000°C. Next, graphitization was carried out at 3100°C, and then the particles were sieved using a 300-mesh screen to obtain flat artificial graphite particles with an average particle size of 27.0 μm for Comparative Example 3.

[0258] The appearance and cross-section of the negative electrode materials of the Examples and Comparative Examples were observed using an electron microscope. It was confirmed that the negative electrode materials prepared in Examples 1-3 have a structure composed of stacked flat graphite particles. It was confirmed that the negative electrode material prepared in Comparative Example 1 comprises particles formed by the aggregation or combination of multiple flat graphite particles with non-parallel main faces. It was confirmed that the flat artificial graphite particles prepared in Comparative Example 3 are flat (flaky) primary particles. Furthermore, it was observed that the negative electrode materials prepared in Examples 1-3 have fewer pores compared to the negative electrode materials of Comparative Examples 1 and 2. Electron microscope images of the appearance and cross-section of the negative electrode material of Example 1 are shown below. Figure 1A and Figure 1B Electron microscope images of the appearance and cross-section of the negative electrode material of Comparative Example 1 are shown below. Figure 2A and Figure 2B Electron microscope images of the appearance and cross-section of the negative electrode material of Comparative Example 2 are shown below. Figure 3A and Figure 3B Electron microscope images of the appearance and cross-section of the negative electrode material of Comparative Example 3 are shown below. Figure 4A and Figure 4B It should be noted that, Figure 2B The cross-sectional image of the negative electrode material in Comparative Example 1 shown is of the negative electrode material compressed to a density of 1.65 g / cm³. 3 The image shows a cross-sectional view, while other microscopic images show the state of the unpressed negative electrode material.

[0259] Fabrication of the negative electrode for lithium-ion secondary batteries

[0260] The negative electrode material (97.6 parts by weight), carboxymethyl cellulose (CMC) (1.2 parts by weight), and styrene-butadiene rubber (SBR) (1.2 parts by weight) of the examples and comparative examples were mixed to prepare a slurry. A coating of 10 g / cm³ was applied to the glossy surface of the electrolytic copper foil. 2 The slurry was coated using a specific method, pre-dried at 90°C for 2 hours, and then adjusted to an electrode density of 1.65 g / cm³ by roller pressing. 3 Then, it is dried at 120°C for 4 hours under a vacuum atmosphere to solidify it, thus obtaining the negative electrode for lithium-ion secondary batteries.

[0261] The Making of Lithium-ion Secondary Batteries

[0262] Using the electrode obtained above as the negative electrode, a coin battery was fabricated using metallic lithium as the counter electrode, a mixture of ethylene carbonate / ethyl methyl carbonate (3:7 volume ratio) and vinylene carbonate (VC) (1.0 wt%) containing 1 M LiPF6 as the electrolyte, a 25 μm thick polyethylene microporous membrane as the separator, and a 250 μm thick copper plate as the spacer.

[0263] Characteristic Evaluation of Anode Materials and Batteries

[0264] The following methods were used to determine the characteristics of the negative electrode materials obtained in the examples and comparative examples, as well as the negative electrodes and lithium-ion secondary batteries made therefrom.

[0265] [Average particle size, particle size distribution D90 / D10, and standard deviation of particle size distribution]

[0266] Using a laser diffraction particle size distribution measuring apparatus (SALD3100, Shimadzu Corporation), the average particle size of the primary particles and the negative electrode material was determined as the particle size (D50) at which the accumulation from the small diameter side in the volumetric particle size distribution reaches 50%. Furthermore, for both the primary particles and the negative electrode material, the particle size distribution D90 / D10 was determined, representing the ratio of the particle size (D90) at which the accumulation from the small diameter side in the volumetric particle size distribution reaches 90% to the particle size (D10) at which the accumulation from the small diameter side reaches 10%. Additionally, the standard deviation of the particle size distribution was determined based on the aforementioned method.

[0267] Specific surface area

[0268] The negative electrode material was filled into the sample cell, and pretreated by heating at 200°C while being degassed under vacuum. Nitrogen gas was adsorbed onto the resulting sample using a gas adsorption device (ASAP2010, manufactured by Shimadzu Corporation). The specific surface area of ​​the resulting sample was determined using the 5-point method and BET analysis.

[0269] [Oil absorption]

[0270] Using an absorbance measuring device (S-500, ASAHISOUKEN Co., Ltd.), 30g of linseed oil was added dropwise to the negative electrode material using a constant-speed burette, and the change in viscosity characteristics was measured by a torque detector. The amount of linseed oil added per 100g of negative electrode material, corresponding to 70% of the maximum torque produced, was defined as the oil absorption (mL / 100g).

[0271] [Saturated tap density]

[0272] 150cm 3 100 cm³ of negative electrode material was added to a graduated flat-bottomed test tube (manufactured by Kurumichi Scientific Instruments Co., Ltd., KRS-406). 3 With the stopper in place, the electrode is dropped from a height of 5 cm. The mass (g) and volume (cm³) of the negative electrode material after the drop are calculated. 3 Calculate the saturated tap density. Repeat the tapping process until the density reaches saturation.

[0273] [Suppressing pressure]

[0274] 3.0g of negative electrode material was filled into a 15mm diameter mold and compressed at a constant speed of 10mm / min using an Autograph (manufactured by Shimadzu Corporation). During compression, the distance from the bottom surface of the negative electrode material to the pressing surface was measured, multiplied by the bottom area of ​​the mold, to obtain the volume of the negative electrode material. The density under pressure was calculated from the obtained volume of the negative electrode material. The Autograph's pressure hammer was equipped with a load sensor to achieve a predetermined density of 1.8g / cm³. 3 The applied pressure (kN / cm) 2 Set to suppressing pressure.

[0275] [Rebound]

[0276] The reference density when using Autograph (manufactured by Shimadzu Corporation) and pressed using the above method is 1.8 g / cm³. 3 The absolute value of the density difference between the rebound negative electrode material and the density of the rebound negative electrode material divided by the density 1.8 g / cm³ 3 Calculate the rebound amount.

[0277] [Peak intensity ratio of rhombohedral structure]

[0278] The peak intensity ratio (P1 / P2) of the rhombohedral structure was calculated based on the intensity ratio of the diffraction lines of the rhombohedral structure (P1: diffraction angle 43.2 degrees) to that of the hexagonal structure (P2: diffraction angle 44.3 degrees) in the X-ray diffraction pattern using CuKα rays.

[0279] [Degree of graphitization]

[0280] The degree of graphitization was determined using the aforementioned method with an X-ray diffraction measuring instrument (X-RAY DIFFRACTIOMETER MultiFlex, Rigaku Corporation).

[0281] Average inter-face spacing (d) 002 )

[0282] In the diffraction pattern obtained by irradiating the sample with X-rays (CuKα rays) and measuring the diffraction lines using a goniometer, the average interplanar spacing (d) is calculated using Bragg's formula based on the diffraction peaks corresponding to the carbon 002 plane that appear around the diffraction angle 2θ reaches 24°–27°. 002 Average inter-plane spacing (d) 002 The following conditions shall be met for determination.

[0283] Source: CuKα rays (wavelength = 0.15418 nm)

[0284] Output: 40kV, 20mA

[0285] Sampling width: 0.010°

[0286] Scanning range: 10°~35°

[0287] Scanning speed: 0.5° / min

[0288] Bragg's formula: 2dsinθ=nλ

[0289] Where d represents the length of one period, θ represents the diffraction angle, n represents the number of reflections, and λ represents the X-ray wavelength.

[0290] [R value determined by Raman spectroscopy]

[0291] The R value was determined using a Raman spectroscopy apparatus (NSR-1000, manufactured by Nippon Spectroscopy Corporation) under the following conditions.

[0292] Laser wavelength: 532nm

[0293] • Irradiation intensity: 1.5mW (measured using a laser power monitor)

[0294] • Measurement range: 830cm -1 ~1940cm -1

[0295] • Irradiation time: 60 seconds

[0296] • Irradiation area: 4μm 2

[0297] Baseline: 1050cm -1 ~1750cm -1

[0298] [Evaluation of high-temperature storage maintenance rate and high-temperature storage recovery rate]

[0299] The fabricated lithium-ion secondary battery was placed in a thermostatic bath set to 25°C and charged at a constant current of 0.2C until the voltage reached 0V (V vs. Li / Li). + Then, it is charged at a constant voltage of 0V until the current reaches 0.02C. Next, after a 30-minute rest, it is discharged at a constant current of 0.2C until the voltage reaches 1.5V (V vs. Li / Li). + After repeating this charge-discharge cycle twice, a constant current charge of 0.2C is applied until the voltage reaches 0V (V vs. Li / Li). + Then, charge the battery at a constant voltage of 0V until the current reaches 0.02C. Place the battery in a constant temperature bath set at 60℃ and store it for 7 days.

[0300] Then, place it in a constant temperature bath set to 25℃ and let it sit for 60 minutes. Perform constant current discharge at a current value of 0.2C until the voltage reaches 1.5V (V vs. Li / Li).+ Next, repeat the charge-discharge cycle once under the above conditions. Repeat the 60°C storage and post-storage capacity verification a total of three times.

[0301] The high-temperature storage maintenance rate and high-temperature storage recovery rate are calculated using the following formulas.

[0302] High-temperature storage retention rate (%) = (first discharge capacity at 25°C after 21 days of storage at 60°C) / (second discharge capacity at 25°C before storage at 60°C) × 100

[0303] High-temperature storage recovery rate (%) = (Second discharge capacity at 25℃ after 21 days of storage at 60℃) / (Second discharge capacity at 25℃ before storage at 60℃) × 100

[0304] [Injection type]

[0305] The electrode density was pressed to 1.65 g / cm³. 3 negative electrode stamping A circular electrode was formed by attaching it to a glass substrate with double-sided tape to create a flat electrode surface without deformation. At the center of this circular electrode, 3 μL of PC (polycarbonate: manufactured by Kishida Chemical Co., Ltd.) was added dropwise using a micropipette, and the injection time until complete saturation was measured. Three identical electrodes were prepared, and the average values ​​of the three measurements are shown in Table 1.

[0306] [Fast charging capacity retention rate]

[0307] The negative electrode obtained above is stamped to have an electrode area of ​​2.00 cm². 2 A 2016-type coin battery was fabricated using a circular electrode made of lithium cobalt oxide coated on aluminum foil as the positive electrode, a mixture of ethylene carbonate / ethyl methyl carbonate (3 / 7 volume ratio) and vinylene carbonate (0.5% by mass) containing 1.0 M LiPF6 as the electrolyte, a 25 μm thick polyethylene microporous membrane as the separator, and spring spacers as spacers. This coin battery was used as an evaluation battery.

[0308] The evaluation batteries were subjected to aging treatment prior to the fast-charging test. Specifically, the evaluation batteries were placed in a constant-temperature bath maintained at 25°C and charged at a constant current of 0.92mA until 4.2V was reached. Then, they were further charged at a constant voltage of 4.2V until the current decayed to the equivalent of 0.046mA. After charging, the batteries were allowed to rest for 10 minutes before being discharged at 0.92mA until 2.75V was reached. This charge and discharge cycle was repeated 5 times.

[0309] Fast charging tests were conducted using aged evaluation batteries. Specifically, the evaluation batteries were placed in a constant temperature bath maintained at 25°C and charged at a constant current of 0.92mA until 4.2V was reached, and the charging capacity was measured (1). After charging, the batteries were allowed to rest for 10 minutes before discharging. Discharging was carried out at 4.6mA until 2.75V was reached. Further, the batteries were charged at a constant current of 6.9mA until 4.2V was reached, and the charging capacity was measured (2). After charging, the batteries were allowed to rest for 10 minutes before discharging at 4.6mA until 2.75V was reached.

[0310] The value obtained by dividing the charging capacity (2) by the charging capacity (1) and multiplying it by 100 is set as the fast charging capacity maintenance rate (%).

[0311] The evaluation results are shown in Table 1. In Table 1, D10, D50, D90, D90 / D10, and the standard deviation of particle size distribution are values ​​for the graphitized anode material.

[0312] [Table 1]

[0313]

[0314] As shown in Table 1, when using the negative electrode materials prepared in Examples 1-3, the liquid injection capability of the negative electrode and the high-temperature resistance of the lithium-ion secondary battery were improved. Furthermore, when using the negative electrode materials prepared in Examples 1-3, the fast-charging capacity retention rate was also improved.

[0315] All documents, patent applications, and technical standards described herein, and the specific circumstances under which each document, patent application, and technical standard is incorporated herein by reference, are incorporated to the same extent.

Claims

1. A negative electrode material for lithium-ion secondary batteries, comprising composite particles having a structure composed of multiple stacked flat graphite particles, wherein the particle size distribution D90 / D10 of the composite particles is 2.0~5.0, and the particle size distribution D90 / D10 of the multiple flat graphite particles is 2.0~4.

4. The composite particle has a structure formed by the superposition or combination of multiple flat graphite particles with their main faces facing each other. The negative electrode material for the lithium-ion secondary battery is obtained by a manufacturing method including the following steps: The process of classifying multiple flat, graphitizable aggregates and removing at least one selected from the group consisting of fine and coarse particles; The process of mixing the graded, flat, graphitizable aggregates with a binder to obtain a mixture; A process of processing the mixture to produce secondary particles having a structure formed by stacking the plurality of flat, graphitizable aggregates; The process of graphitizing the secondary particles to obtain composite particles having a structure composed of multiple stacked flat graphite particles; and The process of classifying the composite particles to remove at least one selected from the group consisting of microparticles and coarse particles.

2. A negative electrode material for lithium-ion secondary batteries, comprising composite particles having a structure composed of multiple stacked flat graphite particles, wherein the particle size distribution D90 / D10 of the multiple flat graphite particles is 2.0~4.

4. The composite particle has a structure formed by the superposition or combination of multiple flat graphite particles with their main faces facing each other. The negative electrode material for the lithium-ion secondary battery is obtained by a manufacturing method including the following steps: The process of classifying multiple flat, graphitizable aggregates and removing at least one selected from the group consisting of fine and coarse particles; The process of mixing the graded, flat, graphitizable aggregates with a binder to obtain a mixture; A process of processing the mixture to produce secondary particles having a structure formed by stacking the plurality of flat, graphitizable aggregates; The process of graphitizing the secondary particles to obtain composite particles having a structure composed of multiple stacked flat graphite particles; and The process of classifying the composite particles to remove at least one selected from the group consisting of microparticles and coarse particles.

3. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the specific surface area of ​​the composite particles, determined by nitrogen adsorption at 77 K, is 0.5 m². 2 / g~2.8m 2 / g.

4. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the specific surface area of ​​the composite particles, determined by nitrogen adsorption at 77 K, is greater than or equal to 0.5 m². 2 / g and less than 2.0m 2 / g.

5. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the degree of graphitization of the composite particles, determined by X-ray diffraction, is 93.0% to 98.0%.

6. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein in the composite particles, the intensity ratio of the diffraction peak P1 of the (101) plane of the rhombohedral structure and the diffraction peak P2 of the (101) plane of the hexagonal crystal structure in the X-ray diffraction pattern based on CuKα rays is less than or equal to 0.

15.

7. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the composite particles are composite particles with low-crystallinity carbon disposed on at least a portion of their surface. The R value of the composite particles containing low-crystallinity carbon, as determined by Raman spectroscopy, is less than or equal to 0.

50.

8. The negative electrode material for lithium-ion secondary batteries according to claim 7, wherein the R value of the composite particles containing low-crystallinity carbon is determined by Raman spectroscopy to be 0.20~0.

50.

9. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the composite particles are composite particles without low-crystallinity carbon deposited on their surface. The R value of the composite particles without low-crystallinity carbon was less than or equal to 0.20 according to Raman spectroscopy.

10. The negative electrode material for lithium-ion secondary batteries according to claim 9, wherein the R value of the composite particles without low-crystallinity carbon is greater than or equal to 0.03 as determined by Raman spectroscopy.

11. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the oil absorption capacity of the composite particles is 15 mL / 100g to 45 mL / 100g.

12. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the composite particles are compressed to a density of 1.8 g / cm³. 3 The pressure was then released, and the density was 1.8 g / cm³. 3 The absolute value of the density difference between the composite particles after pressure release and the density of the composite particles divided by the density 1.8 g / cm³ 3 Therefore, the rebound amount is greater than or equal to 40%.

13. The negative electrode material for lithium-ion secondary batteries according to claim 1 or 2, wherein the aspect ratio of the flat graphite particles is 2 to 20.

14. A negative electrode for a lithium-ion secondary battery, comprising a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises the negative electrode material for a lithium-ion secondary battery as described in any one of claims 1 to 13.

15. A lithium-ion secondary battery comprising a negative electrode, a positive electrode, and an electrolyte as described in claim 14 for a lithium-ion secondary battery.

16. A method for manufacturing a negative electrode material for lithium-ion secondary batteries, comprising: The process of classifying multiple flat, graphitizable aggregates and removing at least one selected from the group consisting of fine and coarse particles; The process of mixing the graded, flat, graphitizable aggregates with a binder to obtain a mixture; A process of processing the mixture to produce secondary particles having a structure formed by stacking the plurality of flat, graphitizable aggregates; The process of graphitizing the secondary particles to obtain composite particles having a structure composed of multiple stacked flat graphite particles; and The process of classifying the composite particles to remove at least one of the groups consisting of fine and coarse particles. The composite particle has a structure formed by the superposition or combination of multiple flat graphite particles with their main faces facing each other. The particle size distribution D90 / D10 of the composite particles is 2.0~5.

0.

17. The method for manufacturing a negative electrode material for a lithium-ion secondary battery according to claim 16, wherein the negative electrode material for a lithium-ion secondary battery is any one of the negative electrode materials for a lithium-ion secondary battery according to claims 1 to 13.

18. The method for manufacturing a negative electrode material for lithium-ion secondary batteries according to claim 16 or 17, wherein the particle size distribution D90 / D10 of the flat, graphitizable aggregate is 2.0 to 4.

4.

19. The method for manufacturing a negative electrode material for a lithium-ion secondary battery according to claim 16 or 17, wherein the bulk density of the graphitized secondary particles is 0.4 g / cm³. 3 ~1.0g / cm 3 .

20. The method for manufacturing a negative electrode material for a lithium-ion secondary battery according to claim 16 or 17, wherein processing the mixture comprises heating the mixture to volatilize the volatile components of the binder.

21. The method for manufacturing a negative electrode material for a lithium-ion secondary battery according to claim 20, comprising reducing the pressure in the atmosphere during the heating process.

22. The method for manufacturing negative electrode material for lithium-ion secondary batteries according to claim 20, wherein the heating temperature during the processing of the mixture is less than or equal to 400°C.

Citation Information

Patent Citations

  • Negative electrode active material for lithium secondary battery, negative electrode including the same and lithium secondary battery

    JP2005302725A

  • Negative electrode material for lithium-ion secondary cell, method for manufacturing negative electrode material for lithium-ion secondary cell, negative electrode material slurry for lithium-ion secondary cell, negative electrode for lithium-ion secondary cell, and lithium-ion secondary cell

    WO2015147012A1

  • Negative electrode material for nonaqueous secondary cells, negative electrode for nonaqueous secondary cells, and nonaqueous secondary cell

    CN101053098A

  • Carbon material, method for producing carbon material, and non-aqueous secondary battery using carbon material

    CN107112536A